Raids, Rewards, and Reputations in the Market for Managerial Talent - Fee, C. Edward; Hadlock, Charles J. (Review of Financial Studies, 2003)
We find that executives who jump to chief executive officer (CEO) positions at new employers come from firms that exhibit above-average stock price performance. This relationship is more pronounced for more senior executives. No such relationship exists for jumps to non-CEO positions. Stock options and restricted stock do not appear to significantly affect the likelihood of jumping ship, but the existence of an “heir apparent” on the management team increases the likelihood that executives will leave for non-CEO positions elsewhere. Hiring grants used to attract managers are correlated with the equity position forfeited at the prior employer and with the prior employer's performance.